HEADS OF DEPARTMENT ADMINISTRATIVE LAW STRATEGIES OF MANAGING SCHOOLS IN TIMES OF CRISIS - Mahlangu, Vimbi Petrus (RADJA PUBLIKA, 2023)
The purpose of this article is to provide schools with the necessary knowledge and skills to manage sustained crises in schools. The role of heads of department (HODs) in administering schools during times of crisis is covered in this article. The Covid-19 crisis has brought to light a new chance to explore the role of HODs, the stakeholders they represent, and how they could progress toward a larger understanding and better response to critical school concerns. As a result, the author's goal in this article is to find out